Hubungan Health Locus of Control dengan Manajemen Diri pada Pasien Stroke - Sumiari, Ni Wayan; Dewi, Ni Luh Putu Thrisna; Mahardika, I Made; Mirayanti, Ni Ketut Ayu; Lisnawati, Ketut; Sanjiwani, Anak Agung Sri (Jurnal Akademika Baiturrahim Jambi, 2025)
Stroke is one of the leading causes of long-term disability and requires continuous management, including rehabilitation and routine follow-up, to prevent recurrence. Optimal recovery depends not only on medical interventions but also on the patient's ability to consistently engage in self-management. One of the psychological factors influencing self-management behavior is the health locus of control, which refers to an individual's belief in their ability to control their health status. This study aims to analyze the relationship between health locus of control and self-management among stroke patients. A descriptive correlational design with a cross-sectional approach was employed, involving 50 respondents selected through total sampling. Data were collected using a standardized questionnaire and analyzed using the Spearman Rank test. The results showed that the majority of respondents (48%) had a moderate level of self-management, and 44% had an internal health locus of control. A significant relationship was found between health locus of control and self-management among stroke patients (p = 0.000), with a correlation coefficient of 0.946 indicating a very strong positive relationship. These findings suggest that the higher an individual’s belief in their ability to control their health, the better their self-management. Therefore, nursing interventions that focus on enhancing health locus of control can serve as an important strategy in the rehabilitation of stroke patients. It is recommended that healthcare professionals, particularly nurses, develop educational programs and psychosocial interventions aimed at strengthening the health locus of control of stroke patients to support long-term success in self-management.